Dragon image in Hungarian folk tale treasury: Anatomy of a contamination - Gombos, Péter; Németh, Csenge Rózsa (MEDIATON OF HUNGARIAN LANGUAGE CULTURE, 2019)
During our research we wanted to know how the image of the dragon is represented in Hungarian folk tales, or more generally in Hungarian popular belief. More closely we were curious how and when the figure of the animal-like (lizard-like) firedrake and the figure of the (man-like) folk tale character who kidnaps girls mingled. We guessed that originally these two types of dragons had existed separately (in stories) and contamination could happen only later, as a result of which we do not wonder today why a flying firedrake kidnaps a wife for himself.For our research we have reviewed from among the first 19th century Hungarian folk tale collections the ones of László Arany, Elek Benedek, János Berze Nagy, János Erdélyi, Arnold Ipolyi, János Kriza, Oszkár Mailand and László Merényi. We have grouped the tales containing dragons found in them and we have drawn our conclusions according to  the figures of the dragons based on the results concerning the time and way of mingling.
Keywords: folk tale; dragon image; contamination; Elek Benedek